165 ETHNIC AND GENDER DIFFERENCES IN PLATELET AGGREGABILITY. (1st January 2006) - Roongsritong, C.; Sadhu, A.; Otahbachi, M.; Simoni, G.; Moeller, J.; Simoni, J.
Abstract : Background: Recent studies suggest that platelet hyperreactivity is the most important factor affecting the clinical outcome in percutaneous coronary intervention (PCI) subjects. Data on ethic variability of platelet aggregability amongst healthy subjects are limited. Methods: We studied platelet aggregation in 32 healthy men and women free of any antiplatelet medications, aged 22-36 years, of Caucasian, Hispanic, and African American origin. In this ex vivo study we investigated biphasic platelet aggregation in response to adenosine-59-diphosphate (ADP) and epinephrine (EPI), as well as lag time and aggregation in response to arachidonic acid (AA) and collagen (COL). In these subjects, the thromboxane synthase polymorphism was determined indirectly by monitoring platelet AA-thromboxane conversion rate. Results: Healthy individuals exhibited considerable variability in aggregation response to agonists. The group most prone to overall aggregation was Caucasian women, followed by Caucasian men (p < .05). Both sexes of Hispanic origin, as compared to Caucasian subjects, had lower platelet aggregation in response to ADP (p < .05), AA (p < .01), and EPI (p < .05) and a similar response to COL. African American men's overall response to all tested agonists revealed a marked (p < .01) aggregation inhibition as compared to all other tested groups. However, this response was more of an individual rather than a group phenomenon, especially with AA and EPI. A similar effect with AA was observed in Hispanics. The observed AA-thromboxane conversion rate indicated that about 40% of Hispanic and at least 50% of African American subjects displayed thromboxane synthase polymorphism. Conclusions: The present study suggests that antiplatelet management in post-PCI be performed on an individual rather that a generalized basis, based on aggregometry. The observed ethnic and gender differences in platelet function indicate that a customized approach may be beneficial in the prevention of platelet-induced thrombosis.